2004
DOI: 10.1111/j.0956-7976.2004.00736.x
|View full text |Cite
|
Sign up to set email alerts
|

Neural Evidence That Vivid Imagining Can Lead to False Remembering

Abstract: ABSTRACT-The imperfect nature of memory is highlighted by the regularity with which people fail to remember, or worse, remember something that never happened. We investigated the formation of a particular type of erroneous memory by monitoring brain activity using functional magnetic resonance imaging during the presentation of words and photos. Participants generated a visual image of a common object in response to each word. Subsequently, they sometimes claimed to have seen photos of specific objects they ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
97
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(107 citation statements)
references
References 29 publications
8
97
1
1
Order By: Relevance
“…Consistent with the reality-monitoring framework described by Johnson and Raye, there is considerable behavioral evidence that imagery can contribute to false memories (see, e.g., Garry, Manning, Loftus, & Sherman, 1996;Goff & Roediger, 1998;Hyman & Billings, 1998;Johnson, Foley, & Leach, 1988), including in the misinformation paradigm (Dobson & Markham, 1993). Gonsalves et al (2004) were among the first to report using f MRI to examine the neural activity associated with the formation of false memories related to reality-monitoring errors (see also Gonsalves & Paller, 2000). Results showed that the formation of false memories was associated with greater activity in anterior cingulate cortex, precuneus, and right inferior parietal cortex than were correct rejections.…”
Section: Stimulimentioning
confidence: 73%
“…Consistent with the reality-monitoring framework described by Johnson and Raye, there is considerable behavioral evidence that imagery can contribute to false memories (see, e.g., Garry, Manning, Loftus, & Sherman, 1996;Goff & Roediger, 1998;Hyman & Billings, 1998;Johnson, Foley, & Leach, 1988), including in the misinformation paradigm (Dobson & Markham, 1993). Gonsalves et al (2004) were among the first to report using f MRI to examine the neural activity associated with the formation of false memories related to reality-monitoring errors (see also Gonsalves & Paller, 2000). Results showed that the formation of false memories was associated with greater activity in anterior cingulate cortex, precuneus, and right inferior parietal cortex than were correct rejections.…”
Section: Stimulimentioning
confidence: 73%
“…The critical result is that participants also classify new, related items as 'old' much more frequently than new, unrelated items; these incorrect responses to the related items constitute evidence for false memories (e.g., [24][25][26][27] ). Other neuroimaging studies have examined false memories that result from confusing perception and imagination 28,29 . For example, after seeing pictures of some objects (e.g., a photo of a car) and imagining others in response to a verbal cue (e.g., 'imagine a ball'), participants sometimes falsely remember that they saw a picture of an item that they only imagined (i.e., a ball).…”
Section: Distinguishing True and False Memories With Neuroimagingmentioning
confidence: 99%
“…A growing number of neuroimaging studies have shown that instructing people to remember actual past events from their personal pasts and imagine hypothetical events that might occur in their personal futures recruits a common core network comprised of medial temporal lobes including hippocampus, medial prefrontal and medial parietal regions including retrosplenial cortex and posterior cingulate, and lateral temporal and lateral parietal regions (e.g., 46 ). Moreover, neuroimaging studies have also shown that cognitive confusions between imagination and memory sometimes reflect increased activity in regions associated with visual imagery during memory encoding or retrieval 28,29 . These findings provide information concerning the neural basis of imagination and memory that could be helpful in further developing jury instructions that explain how and why the former can be mistaken for the latter.…”
Section: Understanding the Neural Basis Of True And False Memoriesmentioning
confidence: 99%
“…The precuneus has been strongly linked to mental imagery, which has been proposed as a key strategy in visual working memory [4,26]. This brain region has been shown to be strongly involved in memory tasks, when the use of mental imagery is encouraged by the stimuli and task demands [9] or when imagery leads to false remembering [12]. In mental imagery of objects the precuneus is more strongly related to a general level of abstraction [11].…”
Section: Introductionmentioning
confidence: 99%